International Capital Markets and Informal Dollar Standards in the CIS and East Asia - Gunther Schnabl (Hamburg Institute of International Economics (HWWA), 2005)
Although most CIS and East Asian countries are de jure classified as free floaters, they de facto pursue (tight) dollar pegs. This paper emphasizes dollar denomination of shortterm and long-term payment flows as reasons for exchange rate stabilization. Based on the analysis of ,competitive depreciations' and ,competitive appreciations` among the CIS and East Asian currencies it is argued that the adherence to a common external anchor currency enhances macroeconomic stability. Finally, the potential of euro and ruble (CIS) as well as yen and yuan (East Asia) to challenge the dollar as anchor currencies in the respective regions is explored.
Keywords: F32; F31; 330; CIS; East Asia; Informal Dollar Standard; Liability Dollarization; Asset Dollarization; Competitive Depreciation; Competitive Appreciation; Wechselkurspolitik; Reservewährung; Währungssubstitution; Wechselkurssystem; GUS-Staaten; Ostasien